2012
DOI: 10.33899/ijvs.2020.167132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Synertox® on broiler health and performance during aflatoxicosis

Abstract: Eighty, one-day-old commercial male broiler chicks (Ross 308), were distributed to four dietary treatments with two replicates of 10 chicks each, to study the effect of Synertox ® on broiler performance during aflatoxicosis. Birds were reared for 42 days. All birds were fed on diet with or without aflatoxin (AF) in feed, and with or without Synertox (ST) (enzymes, organic acids and yeast extract) in water. The treatments were as follow: T1 (0 ppm AF and no ST); T2 (2.5 ppm AF and no ST); T3 (0 ppm AF and 0.5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
3
0
1
Order By: Relevance
“…The obtained results showed that birds treated with Synertox ® revealed no marked alterations in body weight and body weight gain also there were non-significant changes in feed conversion ratio FCR and higher feed consumption from 2 nd week to the end of the experiment. These results are in accordance with Shareef and Omar, (8) who reported that addition of Synertox ® in the drinking water showed a marked elevation in feed consumption with non-significant changes in FCR com-…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The obtained results showed that birds treated with Synertox ® revealed no marked alterations in body weight and body weight gain also there were non-significant changes in feed conversion ratio FCR and higher feed consumption from 2 nd week to the end of the experiment. These results are in accordance with Shareef and Omar, (8) who reported that addition of Synertox ® in the drinking water showed a marked elevation in feed consumption with non-significant changes in FCR com-…”
Section: Discussionsupporting
confidence: 92%
“…This effect might be due to the potency of probiotic bacteria to induce chelate free radicals, capturing reactive oxygen species and inhibiting their cytotoxic activity Lin and Yen, (61) or due to the components that Synertox ® contains, that help in protein digestion. (8) The recorded data showed that chickens given T-Nil Plus ® evoked nonmarked alterations in serum levels of cholesterol, triglycerides, HDL and LDL. These results are in accordance with Zamanizadeh et al (62) ; Jazi et al, (63) and Sohail et al, (64) who reported that serum levels of cholesterol, triglycerides, HDL and LDL were not affected by Saccharomyces cerevisiae supplementation.…”
Section: Efficacy Of T-nil Plus® and Synertox® On Chickenmentioning
confidence: 96%
See 2 more Smart Citations
“…Penerimaan paling rendah berada diperlakuan kontrol infeksi, dikarenakan produksi telur per harinya yang rendah. Perihal tersebut sejalan pada penelitian sebelumnya yang menyampaikan bahwa dalam memberikan dosis probiotik melalui pakan unggas atau air minum adalah 0,1%-0,15% (Rowghani et al, 2007) atau dosis 2% untuk lebih optimal hasil (Shareef & Al-Dabbagh, 2009). Penelitian ini didukung oleh pendapat Lokapirnasari et al, (2019) yang menyatakan bahwa pemberian feed additives berupa probiotik Lactobacillus casei dan L. casei mampu digunakan sebagai alternatif AGP, sebab mampu menurunkan bobot telur dan hen-day production pada ayam petelur.…”
Section: Hasil Dan Pembahasanunclassified